P050 Consensus based practice guidelines for the management and treatment of Juvenile familial Mediterranean fever: the Egyptian College of Paediatric Rheumatology initiative. (11th November 2021) - Salah, S; Lotfy, H; Hassan, M; Abdulhady, H; Salah, H; El Gaafary, M; Abd El-Latif, E; Farag, Y; Eissa, M; Esam Maher, S; Radwan, A; El-Shanawany, Amira T; et al.
Abstract: Background: Familial Mediterranean fever (FMF) is the most common monogenic auto-inflammatory disease, with the highest prevalence amongst Mediterranean countries including Egypt (where there is high carrier rate of MEFV gene), characterized by recurrent attacks of fever and polyserositis. Mutations in the MEFV gene encoding pyrin has been associated with the disease, which causes exaggeration of the inflammatory response through uncontrolled interleukin production. Issuing updated treatment recommendations are vital for the treating healthcare professionals to get well acquainted with its diagnosis & treatment. To produce consensus-based recommendations to guide the early diagnosis, management and follow-up of patients with FMF. Methods: The Patient/Population, Intervention, Comparison, and Outcomes (PICO) questions were developed and refined by the core team. A qualitative synthesis of scientific evidence based on systematic review and clinical experience was conducted to compile evidence for the diagnosis and management of FMF. A consensus process was conducted among the expert panel to generate the final recommendations and grade their strength. 3 rounds of Delphi process were carried out. Results: Following 3 Delphi rounds, recommendations were developed for: early diagnosis, who to treat, treatment targets, genetic testing and its interpretation in association with clinical presentation, treatment of FMF and dealing with acute attacks, monitoring of management, identify treatment response, systemic affection, persistent attacks or inflammation, resistant cases, protracted symptoms, as well as remission status. Algorithm for patients' diagnosis and management is provided. The final document comprises 12 recommendations, each presented with its degree of agreement (0–10), Level of agreement, grade of recommendation and rationale. The degree of agreement was >7/10 in all instances. Conclusion: This guideline provides comprehensive approach to the accurate diagnosis and effective management/monitoring of FMF. It also represents a model for the incorporation of medical genetics practice into the more traditional domains of general medicine.